2011
DOI: 10.1055/s-0031-1280873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Interface Stresses and Strains for Onlay and Inlay Unicompartmental Tibial Components

Abstract: There are several types of designs used for unicompartmental tibial components. The all-plastic inlay component is recessed and it preserves bone around the outer edge of the tibia. For an onlay component, the entire condyle is resected, and the plastic bearing is usually metal-backed, although all-plastic components are also available. The purpose of this study was to investigate the hypothesis that while 6-mm inlay components require less bone removal, the peak stresses and strains at the surface of the bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Small et al assessed the maximum shear stress in 12 positions within 3 cm distal to the tibial component and found that the onlay design generates a more favorable strain distribution [ 49 ]. Walker et al also found that inlays generated six times more peak stress than onlay designs, which would increase to 13.5 times when softer bone was present at the tibia [ 61 ]. Scott et al found that inlay implants had a significant increase in damage at the microscopic level compared with onlay implants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small et al assessed the maximum shear stress in 12 positions within 3 cm distal to the tibial component and found that the onlay design generates a more favorable strain distribution [ 49 ]. Walker et al also found that inlays generated six times more peak stress than onlay designs, which would increase to 13.5 times when softer bone was present at the tibia [ 61 ]. Scott et al found that inlay implants had a significant increase in damage at the microscopic level compared with onlay implants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 b) [ 19 , 43 ]. Studies have shown that inlay components have higher peak stress at the tibial surface compared to onlay components [ 49 , 61 ], which could be explained by the fact that onlay components rest on the cortical bone and that the metal backing distributes forces over the tibia [ 49 , 61 ]. Perhaps, as a result, a higher incidence of tibial subsidence [ 3 , 66 ] and revisions are seen with inlay designs [ 3 , 22 , 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inlays were found to produce strain values which exceeded that of onlays by a factor of 13.5, which was attributed to areas of softer bone at the bone-implant interface. The authors concluded that the metal-backed onlay components were a better option when considering load distribution over the tibial surface [12]. The superior load distribution of the metal-backed onlay design may be a mechanistic explanation for the improved pain relief demonstrated by the onlay components as compared to the inlay devices.…”
Section: Discussionmentioning
confidence: 99%
“…1b). Previous research has suggested that metal-backed onlay components exhibit superior biomechanics [12]. However, to our knowledge, there is no published report that compares the clinical outcomes of these two implants.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that allpolyethylene UKA has a higher revision rate than fixed, metalbacked UKA [9,16,18]. This has been attributed to the transmission of higher stresses to the proximal tibia with allpolyethylene tibial components resulting in loosening, subsidence, and tibial fracture [31,33].…”
Section: Introductionmentioning
confidence: 99%